The business model of journalism start-ups in China - Zhang, Shixin Ivy (Taylor & Francis, 2018)
This study has addressed the emerging business models for journalism start-ups in China. The author proposed a new analytical model to study six components of a business model namely the consumer, the niche, the delivery, the revenue, the funding model, and the profit sharing mode. Applying this model in eight selected cases in China, this article typologies five business models: (1) Platform-oriented News Aggregator; (2) Platform-oriented Service Provider; (3) Content-oriented News Site; (4) Content-oriented Trade Journal; and (5) Content-oriented We-media. The author argues that Chinese journalism start-ups have explored innovative business models in China’s particular political and social context. The state media policy, market and technology are three main driving forces for the business model.